D-dimer to Creatinine Ratio: A Novel Biomarker Associated with Gensini Score in ST-Segment Elevation Myocardial Infarction Patients. (May 2022) - Yang, Jiaojiao; Zhao, Yingjie; Li, Yong; Tang, Jianmin; Zhao, Yipin
Objective: We propose for the first time that D-dimer to creatinine ratio (DCR) may serve as a new clinical biomarker and explore its association with ST-segment elevation myocardial infarction (STEMI). Methods: 347 STEMI patients with complete D-dimer and creatinine were included in the analysis. According to the median of DCR value, patients were divided into the lower DCR group (DCR < 1.402, n = 173) and the higher DCR group (DCR ≥ 1.402, n = 174), and the differences between the two groups were compared. In addition, patients were divided into four groups according to the quartiles of Gensini score: Group 1(Gensini score ≤ 34, n = 88); Group 2(34 < Gensini score ≤ 65, n = 88); Group 3(65 < Gensini score ≤100, n = 87); Group 4(Gensini score ＞100, n = 84). Multivariate linear and multivariate logistic regression analyzes were performed to determine independent predictors of the Gensini score. Results: High DCR group had higher Gensini score compared with the low DCR group ( P  < .05). DCR was positively correlated with Gensini score (r = 0.493, P  < .001). Multiple linear regression analysis showed that Previous MI (r = 11.312, P  = .035) and DCR (r = 5.129, P  < .001) were independent risk factors associated with the Gensini score. Multivariate logistic regression analysis showed that, compared to Group 1, DCR was an independent risk factor in Group 2, Group 3, Group 4 ( P  < .001). Conclusions: As a new and useful clinical biomarker, DCR was positively correlated with coronary Gensini score in STEMI patients.